Implementasi Literasi Digital Dalam Pembelajaran IPS Di SMP Islam Al-Azhar 46 Pati - Noor Indah Supriyati (Sosio-Didaktika: Social Science Education Journal, 2020)
AbstractAdvances in technology and information are very influential on the sharing of sectors of life that causes a wider spread of globalization, causing various positive and negative impacts. Given this condition, students must have the ability to be more careful in sorting out, searching for data collection information from the internet which is commonly called digital literacy. The ability of digital literacy is closely related to social studies learning regarding social issues in the form of events in the community. The research objective analyzes the application of digital literacy in social studies learning. This type of research is qualitative research. The subjects in this study were teachers and students of Al-Azhar 46 Islamic Middle School Pati 2019/2020. Data collection techniques using interviews and supported by the results of previous research Data analysis methods in this study are interactive analysis. The results of research in the form of the implications of the application of digital literacy in the learning process of social studies through Google Classroom, Kahoot, and Quizzleet under the supervision of teachers and parents.Keywords: Aplication, Digital Literacy, Sosial Studies Learning.